Inhibition of invasion and metastasis of human liver cancer HCCLM3 cells by portulacerebroside A. (3rd December 2014) - Ji, Qian; Zheng, Guo-Yin; Xia, Wei; Chen, Jian-Yu; Meng, Xiong-Yu; Zhang, Hong; Rahman, Khalid; Xin, Hai-Liang
Abstract: Context : Portulacerebroside A (PCA) is a novel cerebroside compound isolated from Portulaca oleracea L. (Portulacaceae), an edible and medicinal plant distributed in the temperate and tropical zones worldwide. Objective : This study investigates the effects of PCA in human liver cancer HCCLM3 cells on metastasis and invasion. Materials and methods : After the cells were treated with PCA (2.5, 5, and 10 μg/ml) for 6, 12, 24, or 48 h, adhesion, transwell invasion, and scratch tests were conducted and cell functions were evaluated. Western blot and FQ-RT-PCR assays explored the mechanism of PCA-inhibited invasion and metastasis in the cells. Results : The adhesion rate of the cells was suppressed at 0.5 h (79.4 ± 1.0, 68.7 ± 1.3, and 58.1 ± 1.3%, versus 100 ± 1.5% in the control), 1 h (78.2 ± 1.2, 70.9 ± 1.6, and 55.4 ± 1.9%, versus 100 ± 1.2% in the control), and 1.5 h (71.6 ± 1.1, 62.3 ± 0.9, and 50.4 ± 0.9%, versus 100 ± 1.1% in the control). The 24 h invasion ability was decreased (356.6 ± 11.2, 204.0 ± 17.6, and 113.0 ± 9.5%, versus 443.6 ± 15.4% in the control). The migration capability was also restrained by PCA for 24 h (324.8 ± 25.4, 250.4 ± 21.0, and 126.3 ± 10.1, versus 381.6 ± 30.6 in the control) and 48 h (470.3 ± 34.3, 404.0 ± 19.7, and 201.0 ± 15.4, versus 752.0 ± 63.6 in the control). There was an increase in the mRNA and protein expression levels of TIMP-2 and nm23-H1, inhibition in the mRNA expression of MTA1, MMP-2, and MMP-9, and suppression in the protein expression of MTA1, RhoA, Rac1/Cdc42, MMP-2, but not RhoC and MMP-9. Conclusion : PCA suppresses the invasion and metastasis of HCCLM3 cells possibly by modulation of the mRNA and protein expression of related parameters. This is the first study to reveal a new potential therapeutic application of PCA in antimetastatic therapy for liver cancer.